Nutritional behaviour of (Non-)eSports players – a comparative study - Huth, Christopher (Quality in Sport, 2021)
Demand for eSports has generated considerable attention from the sport, event, and entertainment industries. However, time is spent playing and watching the computer games and is not related to physical activity. The aim of this study is to focus on nutritional behaviour between persons who practice eSports and those who do not practice eSports. A standardized questionnaire was implemented and, in total, 339 completed questionnaires were generated. The results show that participants who are not playing eSports games are significant healthier, doing more sports, are older, have higher incomes, eat more fruits and vegetables, but drink more caffeine and alcohol. In summary, the study shows that playing eSports games tend to have a negative impact on a healthy and sporting lifestyle.